Green finance, mineral resource rents, and industrial growth: exploring environmental trade-offs and mitigating channels in E7 nations - Dinghong, Xu; He, Wuqiang; Ben-Salha, Ousama; Choukaier, Dhouha (Frontiers in Environmental Science, 2025)
Amid growing climate and resource pressures, E7 countries face the urgent challenge of aligning economic growth with ecological sustainability. The current study examines the influence of population growth, industrial development, mineral resource rents, institutional quality, and green finance on environmental sustainability in E7 nations using annual data from 1996 to 2023. Environmental sustainability is measured using the Load Capacity Factor (LCF), contributing to the literature by applying a comprehensive and balance-sensitive metric rarely used in emerging economy contexts. Using 196 observations and advanced panel methods—MMQR, GMM, FGLS, and CCEMG—the analysis addresses key econometric challenges, including endogeneity, slope heterogeneity, non-stationarity, and cross-sectional dependence. Results show that industrial growth consistently harms sustainability, while green finance has a robust, non-linear positive effect, particularly in higher-performing countries. Mineral resource rents improve sustainability in countries with stronger institutions, revealing the moderating role of governance. The CCEMG findings confirm the sensitivity of these effects to common shocks, and GMM models validate the persistence of sustainability outcomes. This study offers robust empirical evidence for policymakers in emerging markets, emphasizing the conditional benefits of green finance and institutional governance in supporting long-term ecological sustainability.